Analysis of the Effectiveness of Artificial Intelligence as a Learning Medium - M. Nur Imansyah; Supriyadin Supriyadin; Andi Prayudi (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The rapid development of Artificial Intelligence (AI) has driven significant transformation in the education sector, particularly in its application as a learning medium. AI offers the potential to enhance learning quality through personalization, automated feedback, and real-time learning analytics. This article aims to analyze the effectiveness of AI as a learning medium based on empirical research findings and systematic reviews published over the last five years. The research employs a literature review method by examining relevant national and international journal articles. The results indicate that AI-based learning media are generally effective in improving learning outcomes, student motivation, and engagement, especially when integrated with appropriate instructional design. However, AI implementation also faces challenges related to infrastructure limitations, teacher readiness, and ethical and data privacy issues. Therefore, comprehensive implementation strategies are required to ensure that AI can be optimally and sustainably utilized as a learning medium.